PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA KUBUS SUKU KATA SISWA SEKOLAH DASAR - Rusminiati, Rusminiati; Halidjah, Siti; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to describe the improvement of starting reading skill using syllable cube to the first grade students of Sekolah Dasar negeri 04 Jelatang. The method of this research is descriptive in form of classroom action research with collaborative particicpation charachteristics. This research is done in three cycles with teacher and students as the subject of this research. The technique of data collecting is in form of observation and document analysis with observation sheet and document analysis sheet as the tool of data collecting. Analysis data is used to calculate the mean of teacher?s ability on planning, teacher?s ability on implementing, and the improvement of reading skill using mean formula. Based on the data analysis, teacher?s ability on planning is 2.67 in the first cycle, 3.02 in the second cycle, and 3.35 in the third cycle. Meanwhile, the teacher?s ability on implementing is 2.85 in the first cycle, 3.14 in the second cycle, and 3.27 in the third cycle. For reading skill, the score is 63.68 in the first cycle, 66.89 in the second cycle, and 71.52 in the third cycle. In conclusion, syllable cube can improve starting reading skill. Keywords: Improving, Starting Reading Skill, Syllable Cube